Cryptic diversity and gene flow among three African agricultural pests: Ceratitis rosa, Ceratitis fasciventris and Ceratitis anonae (Diptera, Tephritidae). Issue 9 (18th March 2013) - Virgilio, M.; Delatte, H.; Quilici, S.; Backeljau, T.; De, M.
Abstract The 'Ceratitis FAR complex' is a species complex of African fruit flies (Diptera, Tephritidae) including the major agricultural pest Ceratitis rosa and the morphologically similar Ceratitis fasciventris and Ceratitis anonae. To resolve their intra‐ and interspecific genetic relationships and to estimate gene flow within this complex, we surveyed allelic variation at 16 microsatellite loci in 27 African populations of the three morphospecies. Interpopulation genetic distances and individual Bayesian assignments distinguished five genotypic clusters: two involving C. rosa (R1, R2; that may occur in sympatry), two involving C. fasciventris (F1, F2; with parapatric distributions) and one involving C. anonae (A). Intra‐ and interspecific patterns of genetic differentiation were not hierarchically structured and genetic differentiation between conspecific clusters (F1–F2 and R1–R2) was higher or comparable with differentiation between heterospecific clusters (e.g. F1‐A or R2‐A). In some cases, gene flow estimates among morphospecies or among heterospecific genotypic clusters were significantly different from zero, showing the lack of reproductive isolation. Genetic differentiation between genotypic clusters was partly supported by morphological differences observed a posteriori in male secondary sexual characters. These results suggest important revisions to current models of ecological niche requirements and invasion risk of the major agricultural pest C. rosa and provide a basis for a taxonomic re‐interpretation of the FAR complex.